Whole-body central processing of lateral line inputs encodes flow direction relative to the center-of-mass - Elias T. Lunsford; Martin Carbo-Tano; Claire Wyart (Proceedings of the National Academy of Sciences, 2026)
From shifting visual scenes to tactile deformations and fluid motion, animals interpret patterns of sensory flow around their body to construct internal models and produce adaptive behavior. Understanding how such transformations are encoded in the brain remains incomplete. To tackle this question, we leverage the lateral line of larval zebrafish as a tractable system sensitive to fluid motion and used to steer navigation, feed, and avoid predators. By presenting stimuli of either direction to neuromasts along the body, we mapped hindbrain responses via high-resolution calcium imaging. Our findings challenge the notion that central lateral line processing lacks topographic structure by revealing a simple, yet powerful principle centered on an egocentric spatial framework: the direction and location of local flow motions are encoded in reference to the animal’s center-of-mass. Brainstem neurons that encode flow toward the center-of-mass broadly project to form bilateral connections onto reticulospinal neurons that coordinate forward locomotion while those that encode flow away from the center-of-mass displayed a more selective and unilateral projection profile to command neurons eliciting turns. This simple representation enables the brain to register complex flow patterns and provides a robust basis for behavioral action selection. Our finding represents a shift from purely somatotopic encoding toward an integrative representation of axial position and directionality along the horizontal plane combined, revealing a central principle for encoding spatiodirectional cues. This study advances our understanding of how complex mechanosensory inputs select appropriate motor outputs via simple egocentric neural maps in the hindbrain.